The race to zero: emission reduction strategies in the sugarcane growing industry in southern Malawi - Cuff, Amy (Department of Environmental and Geographical Science, 2024)
This research explores emission reduction agendas in the sugarcane growing industry in southern Malawi. In doing so, it describes the various actors and their emission reduction agendas, understands relevant drivers for these, interrogates the interaction and collaboration of different actors in attaining them, and explores the relevance of polycentric governance in the emission reduction agendas of the sugarcane growing industry in southern Malawi. The research used qualitative methods including semi-structured interviews and mixed media reviews (reports, policies, websites, and videos). Findings suggest that governance within the sugarcane growing industry's emission reduction agenda has elements of polycentricity, and is characterised by the chaos and complexity of numerous actors working through self-governance with diffusion and linkages towards the achievement of a common goal but lacks coordination or collaboration between actors. Weaknesses were identified in the lack of consistency of focus areas, with divergence in areas for emission reduction including material inputs, electricity, and burning, and poor collaboration between actors. In the context of Malawi, it is suggested that these weaknesses further underscore equity issues amongst actors at global and local scales. Malawi accounts only for 0.005% of the global greenhouse gas emission share, with national emissions in agriculture accounting for 30%. Adding further complexity, sugarcane has a long history in Malawi , with the sector playing an important role in social and economic development and contributing significantly to the country's gross domestic product. The sector is also characterised by political power plays between the state, the private sector and other actors. The research offers recommendations to enhance linkages and collaboration between actors which potentially allow for improved emission reduction strategies and consideration of local contexts and national needs, and equitable share of responsibility of the climate agenda.